The Role of Leadership in Entrepreneurial Development - Ngo Ngoc Minh, (International Journal of Psychosocial Rehabilitation, 2020)
Stepwise Multiple Regression was used as the statistical tool to obtain results from the collected data. There were total seven independent variables, and one dependent variable. The current study has focused on whether effective leadership exerts impact on entrepreneurial development and if leadership is a fundamental component of entrepreneurship. It has also focused on whether Entrepreneurial Leadership is a significant contributory factor to the extent of relationship between Entrepreneurship, Leadership and Entrepreneurial Leadership